(untitled) (Medical Forum Monthly, 2023)
Objective: To assess the prevalence and treatment of malaria in children hospitalized in district hospitals in Pakistan. Study Design: Analytical / descriptive study Place and Duration of Study: This study was conducted at the Pediatrics, Bachakhan Medical Complex Swabi from January 2022-January 2023. Materials and Methods: Data were collected from 100 patients aged 7-14 years who were admitted to district hospitals. All patients had their blood samples checked for malarial parasites and a detailed history was taken. The results were then analyzed by SPSS. Results: The study showed that the prevalence of malaria was 10%, with fever being the most common symptom reported. The most commonly prescribed drugs were quinine, chloroquine, artesunate, and mefloquine. Conclusion: This study demonstrated that malaria is a public health issue in Pakistan and that prompt diagnosis and appropriate treatment are essential for successful control of the disease.